Avaliação do risco para a saúde e sua relevância e integração nas políticas e regulamentação dos nanomateriais/nanotecnologia - Silva, Maria João (2022)
Outline: 1. Nanomaterials and nanotechnologies; 2. Safety assessment of nanomaterials – occupational exposure and consumers exposure (2.1 Case study 1 -titanium dioxide in food; 2.2. Case study 2 – nanocelluloses); 3. Risk assessment and governance in the nanotechnologies arena.